Correlation between Gastric Mucosal Morphologic Patterns and Histopathological Severity of Helicobacter pylori Associated Gastritis Using Conventional Narrow Band Imaging Gastroscopy. (18th May 2015) - Tongtawee, Taweesak; Kaewpitoon, Soraya; Kaewpitoon, Natthawut; Dechsukhum, Chavaboon; Loyd, Ryan A.; Matrakool, Likit
Abstract : Background and Aim . Identifying specific gastric mucosal morphologic patterns useful for detecting Helicobacter pylori associated gastritis and correlation with histopathological severity. Methods . The endoscopists classified the C-NBI gastroscopic findings into 5 gastric mucosal morphologic patterns as follows: type 1: regular arrangement of collecting venules, type 2: cone-shaped gastric pits, type 3: rod-shaped gastric pits with prominent sulci, type 4: ground glass-like morphology, and type 5: dark brown patches with bluish margin and irregular border. Biopsies of all of the cases were then evaluated by 5 pathologists for definitive Helicobacter pylori diagnosis. Result . Type 1 and type 2 patterns were statistically significant in predicting Helicobacter pylori negative status (58/60, P < 0.01 ). Type 3, type 4, and type 5 patterns were statistically significant in predicting Helicobacter pylori positive status (132/140, P < 0.01 ). Furthermore, the sensitivity, specificity, and positive and negative predictive values of type 3, 4, or 5 morphologies for predicting Helicobacter pylori positive were 94.28%, 96.66%, 98.50%, and 87.87%, respectively, correlated well with inflammation grading according to the Sydney classification (P < 0.01 ). Conclusion . Our study suggests that gastric mucosal morphologic patterns in the Helicobacter pylori infected gastric mucosa can be reliably identified using C-NBI gastroscopy with good correlation with inflammation grading.